2009
DOI: 10.1016/j.berh.2008.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Malignancy in systemic lupus erythematosus: what have we learned?

Abstract: What have we learnt about cancer risk in systemic lupus erythematosus (SLE) over the past decade? One important lesson is that data do confirm a slight increased risk in SLE for all cancers combined, compared to the general population. However, it is clear that this is largely driven by an increased risk for hematological malignancies, particularly non-Hodgkin's lymphoma (NHL), although Hodgkin's lymphoma may be increased as well. In addition, there is evidence for a moderately increased risk of lung cancer, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 46 publications
2
36
0
5
Order By: Relevance
“…Several studies have investigated the role of inflammatory diseases in cervical cancer (Bernatsky et al, 2009;Kiss et al, 2010;Simon et al, 2015). The results of a population-based cohort study showed that women with rheumatoid arthritis and systemic lupus erythematosus are 1.5 times more likely to develop cervical dysplasia and cervical cancer (Kim et al, 2014).…”
Section: Inflammatory Diseasementioning
confidence: 99%
“…Several studies have investigated the role of inflammatory diseases in cervical cancer (Bernatsky et al, 2009;Kiss et al, 2010;Simon et al, 2015). The results of a population-based cohort study showed that women with rheumatoid arthritis and systemic lupus erythematosus are 1.5 times more likely to develop cervical dysplasia and cervical cancer (Kim et al, 2014).…”
Section: Inflammatory Diseasementioning
confidence: 99%
“…Common genetic background and Epstein-Barr virus infection may be possible pathogenic factors in this respect. Older age and longer disease duration may be associated with elevated cancer risk in lupus [17,18,[23][24][25] .…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…There may be a slightly increased risk of cancer in SLE patients compared with the general population, but that seems to be mainly due to the increased incidence of haematological malignancies, especially non-Hodgkin's lymphoma 12 13. The underlying mechanism of the association between lupus and malignancy is still uncertain, and medication exposure seems to be the main culprit.…”
Section: Discussionmentioning
confidence: 99%